2017
DOI: 10.1016/j.pss.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optical and meteor head echo measurements using the Middle Atmosphere Alomar Radar System (MAARSY): Data collection and preliminary analysis

Abstract: Highlights• 105 optical meteors simultaneously detected as head echoes by MAARSY are analysed • Radiants measured by radar and optical show median differences of 1.5 degrees.• Optical calibration shows MAARSY detects meteoroids of masses 10 -9 kg -10 -10 kg • Clear trend of larger RCS for brighter meteors at higher heights and larger speeds • Many events show variations in RCS significantly different than optical light curve AbstractThe initial results of a two year simultaneous optical-radar meteor campaign a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
(39 reference statements)
1
26
2
Order By: Relevance
“…The study was performed for meteoroids with different chemical compositions and velocities. Similar research was performed in [4] using the MAARSY radar. In [5], the authors performed a multi-instrumental optical and radio study of non-underdense meteor trails, the ionization of which is significantly higher than the background level at the initial moment.…”
Section: Introductionmentioning
confidence: 72%
“…The study was performed for meteoroids with different chemical compositions and velocities. Similar research was performed in [4] using the MAARSY radar. In [5], the authors performed a multi-instrumental optical and radio study of non-underdense meteor trails, the ionization of which is significantly higher than the background level at the initial moment.…”
Section: Introductionmentioning
confidence: 72%
“…Meteors can be categorized as being either part of a shower or of the back-ground meteor flux. There is a vast amount and variety of meteoroid material entering the atmosphere every day (Ceplecha et al, 1998), and its deposition is highly variable spatially as well as temporally. These variations are attributed to the inconsistency of the meteoroid material density surrounding the Earth, seasonal changes of the atmosphere and the Earth's movement around the Sun, the methods of observing them such as the geographical location of the observing site, and geometrical factors related to the observing instruments' capability and positions of sources.…”
Section: Introductionmentioning
confidence: 99%
“…This extraterrestrial influx changes the metallic composition of the Earth's atmosphere and lower ionosphere. This happens when meteors burn in the dense atmosphere, resulting in the heating and deposition of free metal atoms and ions (Ceplecha et al, 1998). It is now a well-established fact that the permanent ionized metal layer in the lower ionosphere, at around 90-130 km altitude, is due to the ablation of meteors in that region (Plane et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection using visual cameras can only be performed during night compared to radio-based observations which can be performed throughout the day and is 30 suitable for estimation of total meteor activity. A combination of multiple types of observations may also be used (Brown et al, 2017). Kopp, (1997) showed that the thin-layered structured sporadic-E layer (Es) in the Earth's ionosphere, lying between the altitude range of 90-130 km, is mostly consisted of ionized metal atoms FeC, MgC and NaC.…”
Section: Introductionmentioning
confidence: 99%